Central Nervous System Involvement in Common Variable Immunodeficiency: A Case of Acute Unilateral Optic Neuritis in a 26-Year-Old Italian Patient - Abati, Elena; Faravelli, Irene; Magri, Francesca; Govoni, Alessandra; Velardo, Daniele; Gagliardi, Delia; Mauri, Eleonora; Brusa, Roberta; Bresolin, Nereo; Fabio, Giovanna; Comi, Giacomo Pietro; Carrabba, Maria; et al. (Frontiers in Neurology, 2018)
Common Variable Immunodeficiency (CVID) is a group of heterogeneous primary immunodeficiencies sharing defective B lymphocytes maturation and dysregulated immune response and resulting in impaired immunoglobulin production. Clinical picture encompasses increased susceptibility to infections, hematologic malignancies, inflammatory and autoimmune diseases. Neurological manifestations are uncommon and optic neuritis has been previously reported only in one case with bilateral involvement. We hereby report a case of a 26-year-old man affected by CVID undergoing regular immunoglobulin supplementation, who presented with acute unilateral demyelinating optic neuritis and lymphocytic pleocytosis in the cerebrospinal fluid. A variety of infectious, inflammatory and neoplastic conditions were excluded and a diagnosis of clinically isolated optic neuritis was made. The patient was treated with a short course of intravenous steroids with complete symptoms regression. Overall, this case expands our current knowledge about clinical spectrum of complications in CVID and highlights the need for further research about this complex disease.